Peritoneal carcinomatosis, unilateral malignant pleural effusion with bilateral hydronephrosis post-radical gastrectomy in a signet-ring gastric cancer patient: a case report. Issue 2 (3rd March 2020) - Huang, Yuting; Eltelbany, Moemen; Chow, R. Dobbin; Sood, Aseem
ABSTRACT: Gastric cancer is the fifth most common cancer in the world and the third leading cause of cancer-related deaths. Signet-ring cell type is the most malicious subtype. We report a case of advanced stage gastric adenocarcinoma case post-radical gastrectomy who presented with nausea, vomiting, and diarrhea. Though there were no signs of bowel obstruction on abdominal CT and PET imagine studies, and the cytology of body fluid was initially negative, the patient had unilateral malignant pleural effusion, a moderate amount of ascites and bilateral hydronephrosis. After laparoscopic surgery, the patient was diagnosed with local cancer relapse causing jejunojejunal anastomosis obstruction and peritoneal carcinomatosis causing hydronephrosis. We urge broadening the indication of EGD in the evaluation of advanced stage gastric carcinoma to include mechanic bowel obstruction.